Regional analysis of the characteristics and potential risks of bacterial pathogen resistance under high-pressure antibiotic application. (1st September 2022) - Feng, Yang; Qin, Zhenyang; Geng, Yi; Huang, Xiaoli; Ouyang, Ping; Chen, Defang; Guo, Hongrui; Deng, Huidan; Lai, Weimin; Zuo, Zhicai; Fang, Jing; Zhong, Zhijun
Abstract: The study aimed to perform a regional investigation of the antibiotic resistance characteristics (ARCHs) of zoonotic pathogens in environments of high antibiotic pressure to observe the future trend of antibiotic application. In this study, an ARCH analysis of the animal pathogens was conducted in the Sichuan Basin with an area of about 180, 000 km 2 and an estimated high antibiotic application exceeding 2000 tons. A total of 388 bacterial strains from nine species were isolated during 2013–2021. The results showed a dynamic change in the pathogen resistance in the Sichuan Basin with no apparent temporal trend. Fifty-two of 54 antibiotic resistance phenotypes (ARPs) and 180/218 antibiotic resistance genes (ARGs) were detected in this region. The antibiotic resistance in the classification of β-lactam, sulfanilamide, and tetracycline had a relatively high detective rate, with 33–58% of ARPs and about 29.7% of ARGs. The isolates from terrestrial animals generally had higher ARPs and ARGs than aquatic animals. Most pathogens carried 5–11 ARPs, and each isolate carried 19.7 ARGs on average. Our result showed that there was a complicated accumulation of ARGs under high antibiotic pressure. Besides, the unique strain in the Sichuan Basin did not show higher resistance rates compared with the World Health Organization data, possibly due to fitness cost. However, the complex ARCH under high pressure still deserves attention to prevent the emergence of super-resistant bacteria. Graphical abstract: Image 1 Highlights: This study conducted an ARCH analysis of the animal pathogens in the Sichuan Basin. The pathogen showed a dynamic change of resistance with no apparent temporal trend. 52/54 ARPs and 180/218 ARGs were detected in this region. The isolates from terrestrial animals have higher ARPs and ARGs than aquatic animals. Complex ARCH under high pressure deserves attention to prevent the emergence of super-resistant bacteria.